Investigating of solid waste management in Universiti Utara Malaysia-TNB hostel - Ibikunle, Afeez Kayode; Che Abah, Nurul Hanna; Azmi, Farhan Atiqah; Ibrahim, Maryani; Hasbollah, Rasyidah; Rabiat, Adeola Saleeman; Ahmad, Azhar (2015)
This study is to investigate solid waste management in UUM - TNB hostel. More specifically, this research determines the rate of solid wastes generated within UUM-TNB hostels. More so, it looks into the relationship between male and female solid waste generation at UUM-DPP TNB. To achieve these objectives, our respondents will be DPP TNB students, UPSB UUM and DPP TNB management.Besides using a survey to gather appropriate information, this research also employs key personnel perspectives into the analysis.It is expected that the findings could contribute towards greater understanding in view of planning and control. This research is also expected to provide effective information for managerial applications in UNIVERSITI UTARA MALAYSIA.